PENANAMAN NILAI KARAKTER SISWA DALAM KEGIATAN EKSTRAKURIKULER TARI DI SMA NEGERI 5 LUBUKLINGGAU - Frisella Gita Cahyani; Yuliasma (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe and analyze the process of instilling character values in students through dance extracurricular activities at SMA Negeri 5 Lubuklinggau. The research focuses on three dimensions of the Profil Pelajar Pancasila (Pancasila Student Profile): Independence (Mandiri), Mutual Cooperation (Bergotong Royong), and Global Diversity (Berkebinekaan Global). This study employs a descriptive qualitative research model. The primary instrument is the researcher, supported by observation sheets, interviews, and photo and video documentation. The subjects of this research consist of 15 students participating in the dance extracurricular program. The research was conducted over 12 sessions, following the established schedule of the dance extracurricular at SMA Negeri 5 Lubuklinggau on Fridays and Saturdays. The results indicate that dance extracurricular activities effectively serve as a medium for instilling student character values. Through the Tari Rantak material, which was selected by students via a voting process, character values were developed through habitualization (habits) from the first to the twelfth sessions. The dimension of Independence is evidenced by individual accountability regarding time management and movement mastery. Mutual Cooperation is reflected in movement synchronization, team discussions, and student collaboration, while Global Diversity is demonstrated through students' appreciation and enthusiasm for learning dances from other cultures. Despite being conducted during the month of Ramadan, the instillation of character values was consistently achieved. Thus, the cultivation of student character values through dance extracurricular activities at SMA Negeri 5 Lubuklinggau has been successfully implemented.